Leg health and growth performance of broiler chickens supplemented with grape seed extract - Rodríguez Ortega, Leodan T; Rodríguez Ortega, Alejandro; Pro Martínez, Arturo; Sosa Montes, Eliseo; Hernández Guzmán, Filogonio J; Leyva Jimenez, Hector (Revista Colombiana de Ciencias Pecuarias, 2023)
Background: Active bone remodeling processes can be altered by the presence of reactive oxygen species and, therefore, cause leg problems in broiler chickens. The antioxidant activity present in grape seed extract (GSE) could be a viable alternative to high inclusion levels of vitamin E (VE) as a nutritional strategy to improve the antioxidant capacity of birds and, thus, prevent leg abnormalities. Objective: To evaluate the effect of partial substitution of VE with grape GSE on leg health and performance of broiler chickens. Methods: Four hundred and twenty newly-hatched Ross 308 male broiler chickens were distributed into three treatments: 1) Control-AL, a diet containing 40 IU/kg of VE and fed ad libitum (CAL); 2) Control-FR, the CAL diet but offered through a feed restriction program (CFR); and 3) grape seed extract-AL, a diet containing 10 mg/kg of GSE + 10 IU/kg of VE fed ad libitum (GSE-AL). The trial was conducted for 47 days. Feed intake and body weight of the chickens were recorded weekly to evaluate performance. At day 43, gait score (GS), valgus/varus angulation (AngV), foot burn (FB), and hock burn (HB) lesions were evaluated. At day 47, tibia-breaking strength (TBS) and gastrocnemius tendon-breaking strength (GTBS) were evaluated. Results: Birds in the GSE-AL treatment showed reduced (p≤0.05) GS compared to the other treatments. No statistical differences (p>0.05) were found in AngV, HB, FB, TBS, TGBS, and growth performance among treatments. Conclusions: These results suggest that GSE may partially replace VE in broiler diets without negative effects on growth performance or leg health. Further research is required to evaluate the potential of grape seed extract to replace VE or other ingredients with antioxidant activity under different rearing conditions and feeding programs.